A Regulatory and Implementative Study on Women's Rights, Lactation Spaces, and the Role of State Responsibility - Meti Sulastri; Dey Ravena; Sri Ratna Suminar; Neni Ruhaeni (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This study aims to examine and analyze the existence of lactation rooms as a form of legal protection for female workers from the perspective of labor law and health law in Indonesia. Descriptive-analytical method is used in this research, with a juridical-normative approach and qualitative research data. Primary, secondary, and tertiary data are obtained from relevant regulations and literature. The results of this study indicate that the provision of lactation rooms is regulated in Law No. 13 of 2003 on Employment, Law No. 17 of 2023 on Health, and Government Regulation No. 33 of 2012 on Exclusive Breastfeeding and its derivative regulations, the legal provision of lactation rooms remains limited and lacks comprehensive scope. This leads to the absence of adequate facilities in many workplaces, contributing to the low success rate of exclusive breastfeeding among employed mothers. Meanwhile, countries such as Sweden and Singapore, despite lacking explicit regulations mandating lactation rooms, have implemented successful workplace lactation policies through broader worker welfare frameworks. The barriers to implementation in Indonesia include unsupportive organizational culture, insufficient budget allocation, and weak government oversight. This study recommends explicit regulatory reform, widespread policy dissemination, and multi-stakeholder collaboration to strengthen the protection of female workers’ health rights.